Editorial Note - K, mandal (Journal of Meat Science, 2022)
The year 2020 is buoyed by coronavirus pandemic to a larger extent and has brought  unprecedented challenges, and opportunities to reassess and reaffirm our values. However,  Indian Meat Science Association (IMSA) and Journal of Meat Science has started the year 2020  on a positive note through organization of multiple events for various meat sector stakeholders.  The Editorial board is elated to mention that Journal of Meat Science has successfully improved  its National Academy of Agricultural Sciences (NAAS) impact factor from 4.22 to 4.70 with effect  from 1st January, 2021. The Chief Editor and Editor thanks all the members and the authors who  have contributed their research work into our Journal. We look forward for your quality research  contributions in the coming years. Inspite of huge contribution of meat and poultry sector in terms of economy, livelihood  and nutritional security and ensuring uninterrupted supply of chicken, egg and meat even  during COVID pandemic, the sector is criticized for various reasons. Free range natural  production, small-scale animal-agriculture, local production and consumption, less food miles,  water and energy efficient practices etc. are ensuring the sustainability of animal sourced foods  for thousands of year. However, due to lack of good infrastructure for hygienic meat production,  transportation and retailing which is a State subject the sector is constantly targeted by various  agencies. The IMSA is interacting with different policy makers, regulators, State-Governments,  Animal Husbandry Departments and other stakeholders for organizing this sector. In order to address the much needed safety issues due to COVID pandemic and other  changing needs, the livestock and poultry sector must ensure three pronged approaches viz,  constant disease monitoring and surveillance, regular vaccination and implementation of food  safety management system (FSMS). Adoption of good production practices to mitigate the green house gas emission from livestock, water and energy efficient processing technologies, humane  certifications to ensure animal welfare, reduced antibiotics/antibiotic free poultry production  and one health approaches are some of the areas we must work on to ensure the sustainability.  We hope to meet you all in the upcoming X-IMSACON at Meerut, U.P either physically/  virtually or hybrid mode to deliberate important meat sector challenges. We express our sincere  gratitude to all the stakeholders of meat and poultry value chain who ensured an uninterrupted  supply of quality proteins for the wellbeing of millions of consumers during the lockdown. We  salute Covid-19 frontline workers and urge all of you to stay safe.
Keywords: COVID pandemic; (IMSA); (NAAS); (FSMS); X-IMSACON; lockdown